Strategi Dan Pengaruh Promosi Dalam Meningkatkan Penjualan Kacamata Di Optik Jaya Padang - Rina Novalinda (LPPM Universitas Dharma Andalas, 2022)
This scientific paper discusses the strategy and influence of promotion in increasing sales of glasses at Optical Jaya Padang. The aim is to find out the promotion strategy and how much influence the promotion has on sales made by Optical Jaya Padang. The type of research that the author uses is descriptive qualitative, where the methods used are observation and interviews. The author conducted interviews with respondents, the respondents who the authors mean are employees of Optical Jaya. After conducting interviews, the authors make observations or observations that aim to make the data that the author can be more complete and real. From the results of the study, it was found that the promotion carried out by Optical Jaya Padang was very important in increasing sales. The author suggests that Optical Jaya is always consistent in carrying out promotional activities so that the promotions carried out are more effective and can benefit Super Optical.